FINITE ELEMENT ANALYSIS OF PORCELANITE LIGHTWEIGHT AGGREGATE REINFORCED CONCRETE DEEP BEAMS STRENGTHENED BY EXTERNALLY BONDED CARBON FIBER STRIPS - Kaiss F. Sarsam; Nabeel A.M. Al-Bayati; Ahlam S. Mohammed (Journal of Engineering and Sustainable Development, 2017)
A nonlinear finite element analysis carried out to investigate the behavior of a simply supported reinforced concrete deep beams to study their shear behavior after being strengthened by externally bonded carbon fiber composites materials (CFRP). Seven identical porcelanite lightweight aggregate concrete deep beams were analyzed numerically by using ANSYS computer program, two of them were unstrenghtened to serve as reference beams while the remaining five were strengthened using carbon fiber strips in different orientations (vertical, horizontal and inclined) and different number of layers (one and two layers). The locally available natural porcelanite aggregate (from western region of Iraq) was used to produce a structural lightweight aggregate concrete. Two different values of the shear span to depth ratio were adopted. The finite element analysis covers load-midspan deflection behavior, first shear crack and ultimate loads, and the crack pattern of the tested deep beams. Good agreement is obtained with available results which indicate the efficiency of the finite element method used to model the problem.